Cognitive Cooperation for the Downlink of Frequency Reuse Small Cells. (29th November 2010) - Akoum Akoum, Salam Salam; Zwingelstein-Colin Zwingelstein-Colin, Marie Marie; Heath Heath, Robert W. Robert W.; Debbah Debbah, Merouane Merouane
Abstract : We develop a cooperative diversity protocol coded over space, time, and frequency to achieve improved quality of service for mobile users in the downlink of small-cell frequency reuse networks. The proposed protocol, called cooperative frequency reuse (CFR), leverages the cellular frequency reuse concept to create space and frequency diversity among pairs of adjacent base stations. The CFR protocol is compatible with the half-duplex mode and is distributed in the sense that each base station acts in autonomy, without the need of a centralized entity. It is implemented in two phases. During the first phase, each base station independently serves its own users on its dedicated frequency band. It simultaneously listens to the symbols transmitted by neighboring base stations. Cognitive cooperation is introduced in the second phase, where each base station transmits on two frequency bands to the scheduled users in both base stations, by means of an appropriately chosen distributed space time code based on the Golden code. We analyze and discuss the performance of the proposed protocol in terms of bit error rate, probability of outage, and ergodic sum rate under different scenarios. Simulation results show that the proposed protocol yields considerable improvement over direct transmission frequency reuse strategies.